Kemiripan genetik wereng coklat, Nilaparvata lugens Stí¥l. (Homoptera: Delphacidae) populasi Klaten dan Yogyakarta berdasarkan penanda RAPD-PCR - Supriyadi, Supriyadi; Wijayanti, Retno (Perhimpunan Entomologi Indonesia, 2018)
Brown planthopper (Nilaparvata lugens Stí¥l) population from Klaten and Yogyakarta may develop into new biotype, but research on the genetic aspect of these populations is limited. Random amplified polymorphic DNA (RAPD)-PCR technique was used to identify the genetic similarity of brown planthopper population from Klaten and Yogyakarta compared to the population of nearby region. Brown planthopper were collected from paddy field in Klaten, Yogyakarta, Sukoharjo, Boyolali, Karanganyar, Sragen, and Ngawi. Five random primers, namely OPB 01, OPB 07, OPC 04, OPC 08, and OPN 15 were used to amplify the brown planthopper. The present study revealed that five random primers produced DNA band patterns clearly and comparable. However, no primer produced DNA band that could differentiate the brown planthopper population from Klaten and Yogyakarta compare to the population from nearby region. Based on dendrogram, the population from Klaten and Yogyakarta showed a genetic similarity to the nearby population from Sukoharjo, Boyolali and Sragen, except from Karanganyar and Ngawi. Intra-population genetic studies of brown planthopper from Klaten and Yogyakarta may be needed to reveal more genetic characters.